Practical appliation of thetechnology of ultrasonic stabilization of accumulated deformation of circular plates - Baltayev, T.; Kushaliyev, D.; Medvedev, M. (Zhangir khan West Kazakhstan agrarian-technical university, 2017)
The most important task of precision mechanical engineering at the present stage is development of more efficient technological processes of manufacturing parts, providing not only achieving high accuracy at the lowest cost, but also the preservation of the initial indicators of accuracy for the life of the product. The authors consider the method of stabilizing the accumulated deformation of parts based on the application of ultrasonic energy.
Наука и образования № 4 (49) 2017 г
Keywords: The elastic sensing element; circular plate; stabilization; relaxation of stresses; accumulated deformation